Q This chapter seems to imply that Haskell, ML and Scheme are all direct descendents of the LC. In that we can just layer certain abstractions (like numbers, tuples etc) over the top of the raw implementation in LC and we’d end up with these languages. Is this true? Does this extrapolate to most functional languages, are they all just varying complexity implementatins of LC?
λ is shorthand for a function.
Take for example a factorial functin:
int factorial(int n) {
if (n == 0) return 1;
return (n * factorial(n-1));
}
we can express this as:
factorial = λn. if n=0 then 1 else n * factorial(n-1)
generally λn.body
should be read as
the function that, for each n yields body
the λ-calculus is basically this kind of function definition taken to it’s logical conclusion. ie. everything is a function, arguments, functions, the results returned by functions are also functions etc.
The syntax only comprises 3 terms
t ::=
x # variable
λx.t # abstration
t t # application
Programming languages have two levels of structure:
There’s a really nice example about how AST’s can represent programs more simply than concrete syntax because things like operator precedence don’t have to be explicitly specified in trees.
The expression 1 + 2 * 3
can be considered ambiguous unless you know operator
precedence rules. In most languages *
binds tighter than +
. Which means that
this expression can only expand to one tree.
+
/ \
1 *
/ \
2 3
Trees are resolved from the bottom up, so we need to calculate 2*3
before we
can calculate 1 + 6
.
We adopt conventions when writing lambda expressions:
s t u == ((s t) u)
and is the linear representation of the following tree:
λ
/ \
λ u
/ \
s t
the bodies of abstractions are taken to extend as far to the right as possible. So treat the parens like greedy regexps basically:
λx. λy. x y x == λx. (λy. ((x y) x))
!= λx. (λy. (x)) y x
Scope: bound variables are variables used in the body of an abstraction, free variables are not enclosed by an abstraction.
We can say that, for λx. t
: λx
is a binder whose scope is t
.
An occurance of x
is free if it is not bound by an enclosing abstraction on
x
λx. x y
^ ^
| free
bound
A term with no free variables is said to be closed.
A term with no free variables is closed. A closed term is also called a combinator. The simplest one is the identity function a function that when called returns its argument.
id = λx. x;
Operational Semantics: The only way we can compute terms is by applying functions to arguments. This can be broken down to a series of steps where each step means substituting the right hand component for the bound variable in the abstractions body.
This is written as
(λx. t1) t2 ⟶ [x ⟼ t2]t1
Apparently [x ⟼ t2]t1
means **the term obtained by replacing all free
occurrences of x in t1 by t2`
Any term that can be reduced like this is called a redux. and reducing it (like we’ve just done) is called beta-reduction
a term that cannot be reduced any further is called a value
Better example:
(λx. x (λx.x)) (u r) # => u r (λx.x)
A good way to think about this is similar to Ruby lambdas, so λx.x
is
equivalent to -> (x) { x}
, and the (u r)
bit is equivalent to .call(u r)
so if you had the lambda
-> x { x * (x + 1) }.call(42)
Then you can think of that “reducing” to
42 * (42 + 1)
because the function definition, and the calling of the function kind of cancel each other out.
There are different strategies for how to choose which reductions to carry out on each step of the evaluation.
This book uses call by value as that’s the semantics that most programming languages use (except Haskell which is a variation on call by name).
Call by value:
Example:
(λx.x) ((λx.x) (λz.(λx.x) z)) # => replacing the identity function with id:
id (id (λz. id z))
This contains 3 reduxes (terms that can be reduced), the whole term, the sub
term (id (λz. id z))
and the sub term of that id (λz. z)
So using our rules above. We have to reduce the RHS to a value before we can
reduce the whole redux. So, the first redux we can reduce is (id (λz. id z))
.
This reduces to: λz. id z
(because we’re calling the identity function with
the argument λz. id z
and the identity function just returns the argument).
The next reduction we can do is to reduce (id (λz. id z))
.
The book says that this reduces down to λz. id z
but I can’t work out why
based on the rules defined above.
I can’t see how we have reduced any of the right hand terms down to values yet…